Emergence of dynamical disorder and phase metastability in carbon nanobowls. (15th October 2021) - Gaboardi, Mattia; Silverwood, Ian; Braunewell, Balthasar; Siegel, Jay; Fernandez-Alonso, Felix
Abstract: The condensed phases of the carbon-based nanobowl corannulene are herein investigated in the temperature range 200–573 K, combining differential scanning calorimetry, synchrotron X-ray diffraction, and quasielastic neutron-scattering. For the first time, we identify the presence of a well-defined thermal event at 382 K, a figure well below a melting point of 540 K. Contrary to naïve expectation, detailed analysis of the neutron-scattering data below and above this pre-melting transition signals the emergence of correlated stochastic dynamics within both thermodynamically stable solid phases of the material. We find that these are progressively responsible for the suppression of molecular and supramolecular order over mesoscopic length scales, and are associated with the formation of high-symmetry rotor-like states exhibiting localized stochastic motions. Upon cooling from the melt, we have also discovered a robust hysteresis associated with the existence of hitherto-unknown metastable liquid (deep-supercooled) and disordered-solid phases. This behaviour is markedly different from that observed in the quintessential Buckminsterfullerene C60 or other chemically substituted fullerene adducts studied to date at this level of detail. These results evince new and yet-to-tapped opportunities for the use of the stable and metastable phases of carbon-based nanobowls in novel applications exploiting the emergence of dynamical disorder at the nanoscale. Graphical abstract: Image 1